Competitividade e fruticultura no Brasil: o caso do cluster de Juazeiro e Petrolina - Pelição, Thiago Zanon (2004)
This dissertation aims at examining the fruit growing activities in mid-stream São Francisco river, specifically in Juazeiro (BA) and Petrolina (PE). The analysis is based on the concept of cluster as proposed by Michael Porter, on the transaction cost economy and on the model proposed by Elizabeth Farina. The main question here is why Brazil isn t more of a fruit exporter, being one of the greatest world producers and endowed with considerably large comparative advantages. The study won t look into European and American protectionism; rather, trying to identify which actions Brazilian business people and producers can tap in order to enhance business from inside out.